Descriptive Data Visualization Dashboard of LQ45 Stock Price Movements using Pygwalker - Evans Winanda Wirga; Julia Fajaryanti; Akmal Ridho Rabbani; Wisnu Sukma Maulana (Asosiasi Dosen Muda Indonesia, 2025)
This research aims to design and develop a descriptive data visualization dashboard for analyzing stock price movements on the LQ45 index. The interactive dashboard is designed to present a summary of descriptive statistics, historical trends, and stock price volatility of LQ45 constituents. The research method applied refers to the CRISP-DM approach and the Dashboard Design Pattern principle, which includes stock price data collection, descriptive statistical analysis, and effective data visualization design. The results of this research are expected to be a useful tool in providing an overview of historical stock price patterns with an interactive approach.